Relation between dialysis dose and quality of life of patients on peritoneal dialysis - yassine AL BORGI; Amina El Alaoui; Zineb Benlachhab; Wiam Toutti; Mohamed SaghirBahah; Khadija Jerghich; Bardai Ghita; Amal Chouhani Amal Chouhani; Nadia Kabbali; Karima El Rhazi; Tarik Sqalli (RDPLF, 2019)
Objective The interest of our work is to identify the objective parameters that can improve the subjective parameters of the well-being of the patients and to share the experience of the care in our center. Kt / V urea and KDQOL SF 36 scale (Kidney Disease Quality of Life short form 36)were used. Material and methods This is a single-center cross-sectional study conducted in October 2018 among patients treated with peritoneal dialysis, followed for at least six months in the Nephrology Department of Fez University Hospital (Morocco). The quality of life was assessed using the SF-36 (short form) version of the Kidney Disease Quality of Life (KDQOL) scale in its validated Arabic dialect version (1). We used the KDQOL-SF36 results as quantitative variables related to obtaining a Kt / V> 1.7. Results This study included 17 adult patients on peritoneal dialysis of which 35.3% are on automated peritoneal dialysis (APD) and 64.7% are on continuous ambulatory peritoneal dialysis (CAPD). The mean age is 40.8 ± 5 years and the sex ratio is 9H / 8F. In bivariate analysis, we found a significant relationship between dialysis dose and social support. This result could be explained by better adherence in patients with better social support. Conclusion Efforts must be made to achieve the adequacy goals, without losing sight of patients' quality of life. There is also a need for further studies that include more patients and study other parameters such as clinical evaluation, residual renal function and ultrafiltration.    .